Contemporary use of excimer laser in percutaneous coronary intervention with indications, procedural characteristics, complications and outcomes in a university teaching hospital. Issue 1 (16th April 2021) - Jawad-Ul-Qamar, Muhammad; Sharma, Harish; Vetrugno, Vincenzo; Sandhu, Kully; Ludman, Peter F; Doshi, Sagar N; Townend, Jonathan N; Osheiba, Mohammed; Zaphiriou, Alex; Khan, Sohail Q
Abstract : Background: Excimer laser coronary atherectomy (ELCA) can be used as an adjunctive percutaneous coronary intervention treatment for challenging, heavily calcified lesions. Although previous studies have documented high rates of complication and restenosis, these predate the introduction of the smaller 0.9 mm laser catheter. As the coronary complexity has increased, there has been a renewed interest in the ELCA. This study investigates the indications, procedural characteristics, complications and outcomes of ELCA in a contemporary coronary interventional practice. Methods: This single-centre study retrospectively analysed 50 patients treated with ELCA between January 2013 and January 2019. Results: Patients had a mean age of 67.9±11.4 years with a male predominance (65.3%). 25 (50%) cases were performed in patients with stable angina. Failure to deliver the smallest available balloon/microcatheter was the most frequent indication in 32 (64%) cases for ELCA use. 30 (60%) of the procedures were performed via radial access. The 0.9 mm X-80 catheter was used in 41 (82%) of cases, delivering on average 9000±3929 pulses. ELCA-related complications included 2 coronary dissections and 1 perforation, all of which were covered with stents. No major complications could be directly attributed to the use of ELCA. There was one death and one case of stent thrombosis within 30 days of the procedure. Conclusion: ELCA can be performed safely via the radial approach with a 0.9 mm catheter with a high success rate by suitably trained operators. The low procedure-related complications with contemporary techniques make this a very useful tool for complex coronary interventions, especially for difficult to dilate lesions and chronic total occlusion vessels.